Historical Record of the Twelfth, or the East Suffolk, Regiment of Foot : Containing an Account of the Formation of the Regiment in 1685, and of Its Subsequent Services to 1847 - Cannon, Richard, 1779-1865 (Salt Lake City, UT : Project Gutenberg, 2017)
"Historical Record of the Twelfth, or the East Suffolk, Regiment of Foot" by Richard Cannon is a historical account written in the mid-19th century. This work provides a detailed narrative of the formation and military activities of this specific regiment from its inception in 1685 through to 1847. The book likely covers various battles, notable officers, and significant achievements, showcasing the regiment's service over many decades. The opening of the book lays out the premise for documenting the distinguished record of the Twelfth Regiment and emphasizes the importance of such records in preserving military history. It explains how the regiment was formed in response to the political climate in England during the late 17th century, particularly due to the Monmouth Rebellion. Cannon introduces readers to the rigorous service and the key roles that members of the regiment played in various military engagements, setting the stage for a comprehensive exploration of their exploits throughout its history. This establishes a foundational context for readers interested in military history and the specific legacy of this regiment within the British Army. (This is an automatically generated summary.)
Release date is 2017-01-26
E-text prepared by Brian Coe, John Campbell, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Great Britain. Army -- History; Great Britain. Army. Suffolk Regiment